Phenotypic and genetic characterization of B. cinerea Chilean isolates of different levels of fenhexamid sensitivity - ESTERIO, MARCELA; RAMOS, CECILIA; WALKER, ANNE-SOPHIE; FILLINGER, SABINE; LEROUX, PIERRE; AUGER, JAIME (Phytopathologia Mediterranea, 2012)
Forty three Chilean Botrytis cinerea isolates of different fenhexamid sensitivities, obtained from table grapes, were phenotypically analyzed and sequenced for the erg27 gene that encodes the 3-ketoreductaseenzyme. Fifteen isolates were highly resistant to fenhexamid (HydR3+) with conidial germination EC50values >5 μg·mL-1 and colony growth EC50 values >2 μg·mL-1. Five isolates had slight to moderate resistance levels (HydR3-) with conidial germination EC50 values between 0.7 and 2.6 μg·mL-1 and colony growth EC50 values between 0.4 and 3 μg·mL-1. Twenty-three isolates were fenhexamid sensitive (HydS) (conidial germination and colony growth EC50 values <0.1 μg·mL-1). Resistance to anilinopyrimidine (phenotype AniR1), benzimidazole (phenotype BenR1) and dicarboximide fungicides (phenotype ImiR1) was common among isolate stested. When HydR3- and HydR3+ sequences were compared with fenhexamid-resistant French isolates, it was verified that all the HydR3+ had a modification in the C-terminal at position 412 of the protein, close tothe putative transmembrane domain responsible for fenhexamid resistance. The HydR3- isolates showed sixspecific amino acid changes in the sequenced region of the erg27 gene, between positions 199 and 408 of the protein, with three of these described for the first time.